Impact of COVID-19 crisis on the future of work in India - Kapoor, Prerrna P.; Bairagi, Abhijit; Isola, Anita (2020)
ABSTRACT A secondary analysis of socio-economic, cultural, behavioral, and psychological factors affecting the Indian workforce during and post pandemic for predicting the work landscape of the future and informing the development of aligned productivity models. Keywords Workforce, employment, working from home, socio-economic factors, cultural factors, behavioral factors, psychological factors, India ABOUT THE AUTHOR/S We are a three member team from Microsoft IDC. Future of Remote Work is a key priority for our Geography & Leadership and we have started our FY21 journey via this paper that we are submitting for the symposium. Prerrna P. Kapoor Microsoft prkapoo@microsoft.com Abhijit Bairagi Microsoft abairagi@microsoft.com Anita Isola Microsoft anisola@microsoft.com Deepak Menon Microsoft dmenon@microsoft.com Sandeep Srivastava Microsoft sandes@microsoft.com New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).